1985
DOI: 10.1016/s0735-1097(85)80473-3
|View full text |Cite
|
Sign up to set email alerts
|

Methionine intolerance: A possible risk factor for coronary artery disease

Abstract: Homocystinuria, an inherited disorder associated with premature atherosclerosis, represents a severe form of methionine intolerance. To analyze the importance of milder forms of methionine intolerance in the genesis of vascular disease, the relation between provokable methionine intolerance and coronary artery disease was investigated. In a group of 138 men, aged 31 to 65 years (mean 53), referred for cardiac catheterization, plasma homocystine was measured before and 6 hours after an oral l-methionine load (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
6

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(43 citation statements)
references
References 21 publications
2
35
0
6
Order By: Relevance
“…1 4 This study has produced strong evidence that in patients with premature coronary artery disease in our community, impaired homocysteine metabolism occurred at a frequency similar to that which we and others have found in patients with precocious peripheral and cerebrovascular disease. Our findings in the coronary artery patients contrast with results for a similar group of patients reported by Boers et al, 3 while being numerically similar to results reported by Murphy-Chutorian et al 15 We noted the high proportion (4/9) of postmenopausal vascular disease patients who were found to have impaired homocysteine metabolism, although their numbers are too small to be conclusive.…”
Section: Discussionsupporting
confidence: 82%
“…1 4 This study has produced strong evidence that in patients with premature coronary artery disease in our community, impaired homocysteine metabolism occurred at a frequency similar to that which we and others have found in patients with precocious peripheral and cerebrovascular disease. Our findings in the coronary artery patients contrast with results for a similar group of patients reported by Boers et al, 3 while being numerically similar to results reported by Murphy-Chutorian et al 15 We noted the high proportion (4/9) of postmenopausal vascular disease patients who were found to have impaired homocysteine metabolism, although their numbers are too small to be conclusive.…”
Section: Discussionsupporting
confidence: 82%
“…This study design was similar to that of Horowitz et al,8 and the amount of hemodynamic potentiation as measured by the reduced nitroglycerin dose requirement to achieve endpoints was similar for methionine and N-acetylcysteine. Methionine contains no sulfihydryl groups but is a precursor of cysteine ( Figure 3 19,20 Our results further support the hypothesis that nitroglycerin-mediated vasodilatation requires sulfhydryl groups. Methionine alone had no hemodynamic effects in our study population and is not known to have any direct interaction with nitroglycerin.…”
Section: Methioninesupporting
confidence: 80%
“…The overall findings suggest that hyperhomocyst(e)inemia is an independent risk factor for occlusive atherosclerosis; such a conclusion has been advanced by other investigators. [9][10][11][12]32 There 52).…”
Section: Concentration Of Homocyst(e)ine In Plasmamentioning
confidence: 99%
“…8 Moderately elevated basal plasma levels of H(e) (two to five times normal) are observed in certain subjects with CHD who do not exhibit the systemic manifestations of homocystinuric patients.9 Moreover, patients with CHD or with PAOD exhibit higher plasma H(e) levels than control subjects after methionine loading. [10][11][12] In the present paper, using a micromethod adapted for automated determinations, we measured basal levels of H(e) in a group of apparently healthy individuals and in patients with PAOD.…”
mentioning
confidence: 99%